Study of association of reported Nitrogen use efficiency and low Phosphorous tolerance in 3k lines - Romalsawma; Rai, Mayank (Umiam : CPGS-AS, CAU(I), 2024)
The sustainable production of rice is challenged by the need to optimize nitrogen (N) utilization and improve low phosphorus (P) tolerance. Nitrogen use efficiency (NUE) and low phosphorus tolerance are crucial traits that affect rice productivity, resource utilization, and environmental impact. The study aimed to explore the relationship between NUE and phosphorus tolerance in rice, shedding light on the underlying genetic, physiological, and molecular mechanisms. The research methodology involved a multidisciplinary approach, integrating field experiments, greenhouse studies and laboratory analysis. A total of 233 3k rice lines were planted in low phosphorous acidic soil in augmented design. The development of 3k rice genome project (3kRGP) has helped in understanding natural genetic variation in rice as well as for large-scale discovery of new genes/SNPs associated with economically important traits, which will help to accelerate the pace of developing improved rice varieties around the globe to feed the growing population. Data were collected regarding days to 50% flowering, biological yield, tiller number, panicle number and other parameters (12 in total), which were used for scoring their respective individual performance. The 15 best performers and 15 poorest performing lines were then considered for further evaluation in pots under 4 different combinations of N and P after which 10 extremes were selected 5 best and 5 poorest for pot experiment with varying degree of Nitrogen and Phosphorous fertilizer application. This was done to check the differential reaction of extreme genotypes. A total 30 extreme lines were later used for marker-trait association with 29 markers previously reported to be associated with low N tolerance. After evaluation of the 3k lines for their performance under low N and P conditions, it was revealed that 3k126, 3k240, 3k48, 3k215 and 3k174 were the poorest performers, while, 3k297, 3k298, 3k218, 3k33 & 3k100 were the best performing lines respectively. 3k 33, 3k297 and 3k298 showed minor level reduction in tiller number when only N is applied and P is removed, but its performance is reduced upon P application and N removal. And lastly, the absence of both N and P fertilizer led to an even higher rate of reduction in the tiller number and other parameters. The lines that showed the least relative reduction in number of tillers per plant under both N and P deficiencies were 3k48 followed by 3k174 and can be used as donors for P and N use efficiency. Marker trait association through t-test for marker trait analysis showed significant association in 10 markers out of 22 polymorphic markers. Of 10 markers RM12557 showed a significant association with six traits out of 12. RM 13209 showed significant association for 5 traits including with grain yield per plant. RM12569 a showed significant association with four traits. These markers can be used for MAS and further fine mapping of low P tolerance and NUE.
Includes bibliographical references.
Keywords: Rice; Nitrogen